Multi-Faceted Roles of Stress Granules in Viral Infection - Ruihan Zhao; Xiangdong Li (Microorganisms)
Stress granules (SG), dynamic cytoplasmic condensates formed via liquid-liquid phase separation (LLPS), serve as a critical hub for cellular stress adaptation and antiviral defense. By halting non-essential translation and sequestering viral RNA, SG restrict viral replication through multiple mechanisms, including PKR-eIF2α signaling, recruitment of antiviral proteins, and spatial isolation of viral components. However, viruses have evolved sophisticated strategies to subvert SG-mediated defenses, including proteolytic cleavage of SG nucleators, sequestration of core proteins into viral replication complexes, and modulation of stress-responsive pathways. This review highlights the dual roles of SG as both antiviral sentinels and targets of viral manipulation, emphasizing their interplay with innate immunity, autophagy, and apoptosis. Furthermore, viruses exploit SG heterogeneity and crosstalk with RNA granules like processing bodies (P-bodies, PB) to evade host defenses, while viral inclusion bodies (IBs) recruit SG components to create proviral microenvironments. Future research directions include elucidating spatiotemporal SG dynamics in vivo, dissecting compositional heterogeneity, and leveraging advanced technologies to unravel context-specific host-pathogen conflicts. This review about viruses and SG formation helps better understand the virus-host interaction and game process to develop new drug targets. Understanding these mechanisms not only advances virology but also informs innovative strategies to address immune escape mechanisms in viral infections.